STUDI EKSPLORASI PENDIDIKAN KESEHATAN REPRODUKSI ANAK JALANAN DI RUMAH SINGGAH BINAAN PKPR PUSKESMAS JAKARTA TIMUR - Faika Rachmawati; Kenti Friskarini; Lilian Nova susanty; Hendrik Edison; Rachmalina Prasodjo; sahat Manalu (Puslitbang Upaya Kesehatan Masyarakat, 2020)
Abstract Background: Lack of information and basic knowledge of reproductive health cause street children vulnerable to complex problems, one of which is risky sexual behavior. Reproductive health education is an effort to reduce negative impacts and to protect adolescents from the risk of unwanted pregnancy, abortion, sexually transmitted infections (STIs), HIV/AIDS and sexual violence Objective: This study aimed to explore the implementation and barriers of reproductive health education among street children at shelters under the program of PKPR in East Jakarta public health centers in DKI Jakarta Method: This research used qualitative methods. Data were collected by in-depth interviews. There were 20 research informants consisting of program stakeholders for street children and school-aged children health program at the central level, health offices, social services, public health centers, managers of shelters and street children assisted by shelters in East Jakarta. Results: Knowledge of reproductive health among street children was still poor. The implementation of reproductive health education carried out by PKPR in public health centers was still not optimal because it has not reached all street children at the shelter as well as the lack of trained health resources implementing PKPR trained. Conclusion: Efforts are needed to optimize reproductive health education among street children by strengthening commitment and building networks Keywords: reproductive health education, knowledge, PKPR, street children Abstrak Latar belakang: Kurangnya informasi dan pengetahuan dasar mengenai kesehatan reproduksi menyebabkan anak jalanan rentan terhadap permasalahan yang kompleks, salah satunya adalah perilaku seks berisiko. Pendidikan kesehatan reproduksi merupakan salah satu cara untuk mengurangi dampak negatif serta melindungi remaja dari risiko kehamilan yang tidak dikehendaki, aborsi, Infeksi Menular Seksual (IMS), HIV/AIDS dan kekerasan seksual. Tujuan: Penelitian ini bertujuan untuk menggali pelaksanaan dan hambatan pendidikan kesehatan reproduksi pada anak jalanan di rumah singgah binaan PKPR puskesmas wilayah Jakarta Timur di DKI Jakarta Metode: Penelitian ini menggunakan metode kualitatif. Data dikumpulkan dengan wawancara mendalam. Informan penelitian berjumlah 20 orang yang terdiri dari pemegang program anak jalanan dan kesehatan usia remaja dan sekolah di tingkat pusat, Dinas Kesehatan, Dinas Sosial, puskesmas, pengelola rumah singgah dan anak jalanan binaan rumah singgah di Jakarta Timur. Hasil: Pengetahuan anak jalanan tentang kesehatan reproduksi masih kurang. Pelaksanaan pendidikan kesehatan reproduksi yang dilakukan melalui program PKPR puskesmas masih belum maksimal karena belum menjangkau seluruh anak jalanan di rumah singgah serta kurangnya SDM kesehatan pelaksana PKPR yang terlatih. Kesimpulan: Diperlukan upaya untuk memaksimalkan pendidikan kesehatan reproduksi pada anak jalanan dengan memperkuat komitmen dan membangun jejaring Kata kunci: pendidikan kesehatan reproduksi, pengetahuan, PKPR, anak jalanan